2012
DOI: 10.1159/000335740
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Successful Decannulation Using a Tracheostomy Retainer in Patients with Prolonged Weaning and Persisting Respiratory Failure

Abstract: Background: For percutaneously tracheostomized patients with prolonged weaning and persisting respiratory failure, the adequate time point for safe decannulation and switch to noninvasive ventilation is an important clinical issue. Objectives: We aimed to evaluate the usefulness of a tracheostomy retainer (TR) and the predictors of successful decannulation. Methods: We studied 166 of 384 patients with prolonged weaning in whom a TR was inserted into a tracheostoma. Patients were analyzed with regard to success… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 40 publications
0
37
0
5
Order By: Relevance
“…The study by Kenneth B et al specifically included critically ill obese patients with an average body mass index of 41.9 ± 14 [21]. Few studies [8, 13, 20, 23] reported the severity of the illness of included patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study by Kenneth B et al specifically included critically ill obese patients with an average body mass index of 41.9 ± 14 [21]. Few studies [8, 13, 20, 23] reported the severity of the illness of included patients.…”
Section: Resultsmentioning
confidence: 99%
“…There were 2 studies each with tracheostomies performed by either surgical [8] or percutaneous [20] technique, while 5 studies included patients with both techniques [13, 14, 19, 21, 25]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Removal of the tracheostomy tube in the patient with SCI requires assessment of cough effectiveness, airway patency and adequacy of the swallow [129, 130]. Other considerations such as co-operation of the patient, oxygen requirements, medical stability, presence of respiratory infection or pending surgery should be taken into account [131, 132].…”
Section: Respiratory Treatmentmentioning
confidence: 99%